2014
DOI: 10.1380/ejssnt.2014.404
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Phosphate Ions from Aqueous Solution of Nickel Hydroxides Calcined at Different Temperatures

Abstract: Nickel hydroxide (Ni100) and nickel hydroxide, including cobalt (NiCo91), were calcined at different temperatures. These materials were investigated by analyzing data obtained from X-ray diffraction (XRD), scanning electron microscopy, specific surface area, thermogravimetric-differential thermal (TG-DTA) technique, and electron-probe microanalysis. The XRD and TG-DTA data obtained indicated that calcination at 250-270 • C can promote the conversion of Ni(OH)2 into NiO, and that cobalt hardly affected the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…This linear relationship suggests that the phosphate ions were exchanged with the surface hydroxyl groups of the adsorbents. A similar adsorption mechanism for powdered NiCo91-270 was reported previously [28]. Further studies are needed to elucidate the relationship between the amount of adsorbed phosphate ions and the properties of adsorbents.…”
Section: Amount Of Adsorbed Phosphate Ionssupporting
confidence: 74%
See 4 more Smart Citations
“…This linear relationship suggests that the phosphate ions were exchanged with the surface hydroxyl groups of the adsorbents. A similar adsorption mechanism for powdered NiCo91-270 was reported previously [28]. Further studies are needed to elucidate the relationship between the amount of adsorbed phosphate ions and the properties of adsorbents.…”
Section: Amount Of Adsorbed Phosphate Ionssupporting
confidence: 74%
“…The adsorbent (NiCo91-270) consisted of spherical particles of various diameters, while the PET surface was smooth. In addition, our previous study showed that calcination hardly affected the surface morphology of NiCo91 [28], which could be granulated with PET in this study (under the experimental conditions used herein). We could also observe each adsorbent particle on the granulated adsorbent, indicating that the PET binder did not completely mask the NiCo91-270 surface.…”
Section: Properties Of Granulated Materialsmentioning
confidence: 50%
See 3 more Smart Citations